The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1088/1361-6560/aaecfc
|View full text |Cite
|
Sign up to set email alerts
|

Motion effects in proton treatments of hepatocellular carcinoma—4D robustly optimised pencil beam scanning plans versus double scattering plans

Abstract: Pencil beam scanning (PBS) proton therapy enables better dose conformality for complex anatomical geometries than passive proton scattering techniques, but is more susceptible to organ motion. This becomes an issue when treating moving tumours in the thorax or abdomen. Novel four-dimensional treatment planning approaches have been developed to increase the robustness of PBS plans against motion. However, their efficacy still needs to be examined by means of 4D dynamically accumulated dose (4DDD) analyses.This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…Although PBS offers superior dose conformality, it is more susceptible to differences in tissue electron density and therefore is inherently less robust than PS. Nonetheless, robust PBS plans can be achieved provided that motion-robust planning and motion management techniques are used (60,61). In fact, a recent study from Germany showed that 4D-optimized PBS plans provided better sparing of organs at risk than those created with PS (61).…”
Section: Proton Therapy For Liver Metastasesmentioning
confidence: 99%
“…Although PBS offers superior dose conformality, it is more susceptible to differences in tissue electron density and therefore is inherently less robust than PS. Nonetheless, robust PBS plans can be achieved provided that motion-robust planning and motion management techniques are used (60,61). In fact, a recent study from Germany showed that 4D-optimized PBS plans provided better sparing of organs at risk than those created with PS (61).…”
Section: Proton Therapy For Liver Metastasesmentioning
confidence: 99%
“…Although the investigated case is only limited to one plan and one target, the results can be compared with evaluation of clinical cases. In Pfeiler et al 25 various liver targets with variable motion amplitudes were investigated. The 4DDD was calculated based on a clinical 4DCT and averaged over 60 different starting phases and layer‐switching times.…”
Section: Discussionmentioning
confidence: 99%
“…The isocenter shift applied to the RO was set to 3 mm (e.g. Pfeiler et al 41 applied a 2 mm). This approach is not sufficient for structures such as stomach or bowels.…”
Section: Discussionmentioning
confidence: 99%